Photophysical and photochemical properties of a family of isoelectronic tris chelated ruthenium(ii) aza-/azo-aromatic complexes. Issue 90 (2nd October 2015) - Das, Samir; Pradhan, Basudev
<x xml:space="preserve">Abstract</x> We have investigated the electrochemical, spectroscopic and electroluminescent properties of a family of aza-aromatic complexes of ruthenium of type [RuII(bpy/phen)2(L)]2+ (4d6) with three isomeric L ligands.